Biomass and nutrient release dynamics of decomposing rolling down legume cover crops in a steep-sloped Mediterranean vineyard - Brito, Cátia; Martins, Sandra; Saraiva, Francisco; Roque, João; Arrobas, Margarida; Rodrigues, Manuel; Correia, Carlos (Frontiers in Agronomy, 2025)
Well-managed cover crops are gaining traction as an alternative to conventional tillage, offering a range of agronomic and ecological benefits. This field study, conducted in a commercial vineyard in the Douro region (Portugal) during the 2022/2023 growing season, evaluated the decomposition dynamics and nutrient release from different legume cover crop residues over a period of 183 days after sowing and 114 days after rolling. These mixtures consisted of subterranean clovers (SC), low-growing (LG), and moderately-growing (MG) legumes. MG legumes produced the highest biomass (7.8 t ha−1), followed by LG (7.2 t ha−1) and SC (5.9 kg ha−1). MG residues decomposed more rapidly, potentially meeting early grapevine nutrient demands. SC residues decomposed more slowly, retaining nutrients over longer periods and acting as a sustained source of fertility, while LG legumes provided a balance between rapid and gradual nutrient release. Biomass production peaked before rolling termination, suggesting that the lower canopy foliage might have started decomposing as the crops reached maximum vegetative expansion and early seed formation, reflecting the dry, hot environmental conditions during the study year. The observed nutrient release from cover crop residues, particularly during the first 45 days post-termination, suggested a potential to support grapevine nutrient requirements, although direct uptake by grapevines was not assessed in this study. SC residues retained higher levels of key macronutrients and micronutrients over time. These findings highlight the importance of selecting legume cover crop mixtures aligned with vineyard management goals, whether rapid nutrient supply or sustained soil fertility. The study also underscores the influence of environmental conditions, residue composition and termination timing on nutrient dynamics. Long-term research is recommended to evaluate cover crops’ chemical composition, cumulative effects on soil organic carbon (C) and nutrients, microbial activity and effects on grapevine performance across diverse Mediterranean environments.